EUGENIO COSERIU AND HIS DISCIPLES ON THE ISSUE OF SYNONYMY - Dr. Cristinel MUNTEANU (Diversitate si Identitate Culturala in Europa)
In this paper we aim to briefly review Eugenio Coseriu’s ideas regarding synonymy and some Coserian disciples’ contributions (be they direct or indirect) concerning this issue. The largest part of this article, however, presents our own contribution to the study of synonymy, whose starting point was Coseriu’s integral linguistics, considered as an epistemological frame of reference. We have tried to apply, within the general study of synonymy (lexical, phraseological and lexico-phraseological), distinctions such as: language as activity [enérgeia], competence [dýnamis] and product [érgon] to its three levels (universal, historical and individual); norm and system; historical language and functional language , etc. As far as we are concerned, we were interested in pointing out, for each of Coseriu’s levels in turn, the difference between synonymy in actu (the real one) and synonymy in potentia (the virtual or potential one). We also aimed at drawing attention to the importance of competence (mainly the idiomatic and expressive ones) in the analysis of different types of synonymy as “knowledge” in using the synonyms.